IMPLEMENTASI MEDIA PEMBELAJARAN KONTEKSTUAL BERBASIS LINGKUNGAN SOSIAL UNTUK SEKOLAH MENENGAH PERTAMA - Hidayah Budi Qur'ani; Purwati Anggraini (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2019)
This research is a case study at Muhammadiyah 2 Middle School in Batu. The results of the interviews and questionnaires showed that the teachers had difficulty in making learning media when using a contextual approach. This is due to the teacher's limited ability to utilize learning media. Therefore, this study offers a solution to the use of contextual media based on the social environment that can be used by teachers to teach material that must be associated with everyday life. The solution offered is the use of visual learning media in the form of photos relating to community social activities and audio-visual learning media in the form of videos related to changes in the social behavior of the community. Keywords: learning media, contextual, social environment, junior high school